Parallel implementation of a meshfree method for calculating flows of ideal incompressible fluid - Govorukhin, V.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
A parallel algorithm for calculating the two-dimensional dynamics of inviscid incompressible fluids on a rotating sphere is proposed. The algorithm is based on the meshfree vortex-in-cell method for solving an initial boundary value problem for unsteady equations describing the motion of an ideal fluid in terms of the absolute vorticity and stream function. The method is based on the approximation of the stream function using the Fourier series. The vorticity field is defined by its values on a set of particles. The particle trajectories are calculated using a pseudo-symplectic integrator. At each time step, the parallelization involves the splitting into subsets of particles and the decomposition of the flow region. The efficiency of the parallel algorithm and its performance are evaluated experimentally for various parameters of the method. The numerical results show a good scalability of the algorithm.